The relationship between temperature variables and fruit maturity of 'Bon Chretien' pears in four areas in the Western Cape - Frick, Theodora Christina (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 1995.